Eye-Tracking Methodology and Applications in Consumer Research - Hayk Khachatryan; Alicia L. Rihn (EDIS)
Eye-tracking technology is a means of exploring the relationship between visual attention and consumer behavior. In the past, eye-tracking technology has been used to conduct research on consumer decision-making, marketing, and advertising. This 5-page fact sheet serves as an introduction to eye-tracking technology and methodology. Written by Hayk Khachatryan and Alicia L. Rihn, and published by the UF Department of Food and Resource Economics, July 2014.